2017
DOI: 10.3762/bjoc.13.11
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic displacement reactions of 5′-derivatised nucleosides in a vibration ball mill

Abstract: Vibration ball-milling in a zirconia-lined vessel afforded clean and quantitative nucleophilic displacement reactions between 4-methoxybenzylthiolate salts and nucleoside 5′-halides or 5′-tosylates in five to 60 minutes. Under these conditions, commonly-encountered nucleoside cyclisation byproducts (especially of purine nucleosides) were not observed. Liquid-assisted grinding of the same 5'-iodide and 5′-tosylate substrates with potassium selenocyanate in the presence of DMF produced the corresponding 5′-selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…62 In the presence of excess potassium selenocyanate, clean transformation of 5 0tosylthymidine (1) into the corresponding 5 0 -selenocyanate (2) was observed within 90 minutes following irradiation (20 W, 100 C) of the stirred reaction mixture in acetonitrile (Scheme 1). As previously observed, 60 quenching of the excess selenocyanate with benzyl bromide greatly facilitated subsequent purication by silica gel chromatography and pure 5 0 -deoxythymidine 5 0 -selenocyanate (2) was isolated in 75% yield.…”
Section: Preparation Of Dinucleotide Phosphoramiditessupporting
confidence: 61%
See 1 more Smart Citation
“…62 In the presence of excess potassium selenocyanate, clean transformation of 5 0tosylthymidine (1) into the corresponding 5 0 -selenocyanate (2) was observed within 90 minutes following irradiation (20 W, 100 C) of the stirred reaction mixture in acetonitrile (Scheme 1). As previously observed, 60 quenching of the excess selenocyanate with benzyl bromide greatly facilitated subsequent purication by silica gel chromatography and pure 5 0 -deoxythymidine 5 0 -selenocyanate (2) was isolated in 75% yield.…”
Section: Preparation Of Dinucleotide Phosphoramiditessupporting
confidence: 61%
“…5 0 -Deoxythymidine-5 0 -selenocyanate has been prepared on small scales in solution over 24 hours 59 or using liquid assisted grinding over 9-11 hours. 60,61 In order to prepare this material more efficiently, we therefore examined the application of microwaves which has been reported to enhance the rate of Sselective alkylation of the thiocyanate anion. 62 In the presence of excess potassium selenocyanate, clean transformation of 5 0tosylthymidine (1) into the corresponding 5 0 -selenocyanate (2) was observed within 90 minutes following irradiation (20 W, 100 C) of the stirred reaction mixture in acetonitrile (Scheme 1).…”
Section: Preparation Of Dinucleotide Phosphoramiditesmentioning
confidence: 99%
“…Expeditious displacement of tosylate or halides from 5′-derivatised nucleosides was achieved using chalogenate nucleophiles in a mixer ball mill using zirconia components [ 22 ]. Highly efficient transformations to the corresponding 4-methoxybenzyl thioethers were achieved in 15–60 minutes such that pure products could be isolated without the need for chromatography ( Scheme 7 ).…”
Section: Reviewmentioning
confidence: 99%
“…During a study of amide coupling under ball-milling conditions, Lamaty and co-workers showed that deterioration of vessels and balls by physical abrasion and/or chemical leaching gave products in which (depending upon the nature of the jar) iron, chromium, zirconia or PTFE were detected [ 20 ]. This has influenced the choice of vessel for nucleoside and nucleotide chemistry as, although considerably cheaper, leaching of iron from stainless steel vessels in the presence of sulfur-containing materials [ 21 ] has been found to inhibit the preparation of thionucleoside [ 22 ] or thionucleotide [ 23 ] analogues. Although grinding using PTFE components delivers less energy due to the material’s elasticity and low density (2.1 g cm −3 ) compared with stainless steel (7.8 g cm −3 ) or zirconia (5.9 g cm −3 ), PTFE may be required for the preparation of pharmaceutical grade materials which are subject to regulatory approval.…”
Section: Introductionmentioning
confidence: 99%
“…The groups of Reese (Divakar & Reese, ; Divakar, Mottoh, Reese, & Sanghvi, ; Marriott, Mottahedeh, & Reese, ) and Engels (Jahn‐Hofmann & Engels, ) have described solution‐phase chemistry for the preparation of thionucleosides in which the thiol function is masked by an acid‐sensitive group (e.g., 4‐methoxybenzyl, t ‐butyl, dimethoxytrityl, or thiopixyl) and one‐pot deprotection‐activation is employed, as S ‐aryl disulfides of both nucleoside and peptide substrates under acid conditions have been described. (Divakar et al., ; Schroll, Hondal, & Flemer, ) The application of such disulfides for the preparation of internucleoside phosphorothiolate linkages via Michaelis‐Arbuzov chemistry is well established (Gaynor & Cosstick, ; Li et al., ; Vyle, Li, & Cosstick, ) and was adapted by our group for the preparation of a stable, silylated intermediate (Eguaogie et al., ; Eguaogie et al., ) from which the target pyrophosphorothiolate‐linked dinucleoside analog was accessed using mechanochemistry. In contrast to solution‐phase mixing of reagents and substrates under standard conditions, grinding has only recently been explored in the context of organic chemistry using vibration ball milling (Wang, ), planetary ball milling (Do & Friščić, ), or single‐/twin‐screw extrusion (Crawford, ).…”
Section: Introductionmentioning
confidence: 99%